Alubijid river basin hydrologic modeling in Misamis Oriental in flood risk management - Puno, George R. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2016)
Flood modeling studies for the purpose of forecasting, early warning, and disaster management of the local government and other disaster agencies have been done in many countries nowadays. With a similar rationale, this study aims to assess the precipitation-runoff capacity of the Alubijid River Basin which can be put a significant number of 41,936 populations at risk to flooding. Using the 10-meter resolution SAR-DEM, the drainage system of the river basin was delineated in ArcMap 10.1 with the aid of HEC-GeoHMS. Data were collected last November 26-27, 2014 during the "Typhoon Queenie" which contributes to water level rise at 1.04 meter MSL of 86.7 mm accumulated rainfall with a peak discharge of 18.7 m3/s. The hydrologic data and generated basin model were inputted in HEC-HMS for calibration. After series of manual adjusting the river basin's parameters, the hydrologic modeling revealed that the river basin was accepted based on the conducted model validation and performance rating. The overall statistical measures conducted obtained very good and satisfactory ratings. As a result, the basin model is accepted for water level monitoring and forecasting as it gives lead time for the preparation of evacuation of the vulnerable community to the safe sites identified by the local government unit.